Social Connectedness and Movements Among Communities of Giraffes Vary by Sex and Age Class - Lavista Ferres, Juan M.; Lee, Derek E.; Nasir, Md; Chen, Yu-Chia; Bijral, Avleen; Bercovitch, Fred B.; Bond, Monica L. (Animal Behaviour, 2021)
Many social mammals form discrete social communities within larger populations. For nonterritorial, polygynous, size-dimorphic species, sex- and age-class differences in life-history requirements might mediate differences in social connectedness and transitions among communities. We conducted social network analysis and community detection with an extensive data set of 1081 individually identified wild giraffes, Giraffa camelopardalis, over 5 years to test predictions that adult males and young of both sexes show greater social connectedness (degree, closeness and betweenness centrality) and transition more often among social communities than adult females, which form stronger and more stable relationships. We also expected that young animals would be more socially connected than adults. Using both static and dynamic network clustering techniques, we detected four distinct mixed-sex social communities, which we termed ‘super-communities’ to differentiate this apex level of social organization from intermediate-level female-only communities. Most (∼70%) giraffes remained within their same super-community, and those (usually adult males) that visited a different super-community often returned to their original super-community. Males – both adults and calves – had higher social centrality scores than females, and adult males were closer to all other individuals in the network and transitioned among super-communities twice as often as females and calves, reflecting their roaming reproductive strategy of seeking females in oestrus. Of all age and sex classes, young males had the most social ties and highest betweenness (moved most often among groups), which we attributed to social exploration prior to natal dispersal. Overall, female giraffes have stronger social associations than males, but males exceed females in measures of social connectedness, reflecting differences in reproductive and life-history profiles. Our findings suggest that giraffe translocations that do not consider sociality are likely to break up established social associations and potentially reduce fitness.